Descriptors for hazelnut (Corylus avellana L.) - Bioversity International; Food and Agriculture Organization of the United Nations; International Centre for Advanced Mediterranean Agronomic Studies (Bioversity International, 2008)
Descriptors for hazelnut, or filbert, (Corylus avellana L.) were developed by Professor Dr A. Ilhami Koksal and Dr Nurdan Tuna Gunes. An advanced draft was subsequently prepared by a group of experts within the FAO-CIHEAM Interregional Cooperative Research Network on Nut trees, coordinated by Dr Ignasi Batlle. The document was harmonized as far as possible with descriptors developed by the International Union for the Protection of New Varieties of Plants (UPOV, 1979). This revised document was subsequently sent to a number of experts for their comments. A full list of the names and addresses of those involved is given in the 'Contributors' Section.